Advancing Ecological Justice through the Integration of Eco-Religion in Criminal Law Reform - Fernando, Zico Junius; Dahwal, Sirman; Arifin , Firdaus; Maskur , Muhammad Azil; Muthia, Arini Azka (Ius et Ambientis, 2025)
The accelerating global ecological crisis has exposed the limitations of anthropocentric and utilitarian paradigms embedded in conventional environmental criminal law. This article proposes the integration of eco-religion a spiritual worldview that regards nature as sacred and interdependent with human moral responsibility as a transformative foundation for ecological justice and legal reform. Drawing upon Islamic, Christian, Hindu-Buddhist, and indigenous environmental ethics, the study argues that spiritual values can provide normative depth and cultural legitimacy to reorient criminal law from a punitive model toward a restorative and justice-oriented framework. Utilizing a normative legal method enriched by conceptual, comparative, and futuristic approaches, the paper analyzes key international practices including those in Ecuador, Bhutan, France, and Uganda and explores their applicability to the Indonesian context. The study demonstrates that incorporating eco-religious values can elevate the legal standing of nature, reframe environmental crimes as moral transgressions, and empower local wisdom and constitutional principles such as Pancasila and the 1945 Constitution. Ultimately, this integration offers a culturally rooted and ethically grounded model of legal reform that redefines environmental harm as a crime against life systems, calling for accountability, restoration, and intergenerational justice.